AI, data and private law : translating theory into practice - Chan, Gary Kok Yew; Yip, Man (New York: Hart Publishing, 2021)
'This book examines the interconnections between artificial intelligence, data governance and private law rules with a comparative focus on selected jurisdictions in the Asia-Pacific region. The chapters discuss the myriad challenges of translating and adapting theory, doctrines and concepts to practice in the Asia-Pacific region given their differing circumstances, challenges and national interests. The contributors are legal experts from the UK, Israel, Korea, and Singapore with extensive academic and practical experience. The essays in this collection cover a wide range of topics, including data protection and governance, data trusts, information fiduciaries, medical AI, the regulation of autonomous vehicles, the use of blockchain technology in land administration, the regulation of digital assets and contract formation issues arising from AI applications. The book will be of interest to members of the judiciary, policy makers and academics who specialise in AI, data governance and/or private law or who work at the intersection of these three areas, as well as legal technologists and practising lawyers in the Asia-Pacific, the UK and the US'--
AI, data and private law : the theory-practice interface / Gary Chan Kok Yew and Man Yip -- How to de-identify personal data in South Korea : an evolutionary tale / Haksoo Ko and Sangchul Park -- Data trusts for lawful AI data sharing / Chris Reed -- The future of personal data protection law in Singapore : a role for the use of AI and the propertisation of personal data / Warren Chik -- Personal data as a proprietary resource / Lee Pey Woan -- Transplanting the concept of digital information fiduciary? / Man Yip -- Regulating autonomous vehicles : liability paradigms and value choices / Chen Siyuan -- Medical AI, standard of care in negligence and Tort Law / Gary Chan Kok Yew -- Contractual consent in the age of machine learning / Goh Yihan -- Digital assets : balancing liquidity with other considerations / Gal Acrich, Katia Litvak, On Dvori, Ophir Samuelov and Dov Greenbaum -- Blockchain in land administration? : Overlooked details in translating theory into practice / Alvin W-L See.
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ CIP/ Areesh Education & Trading
Includes bibliographical references and index. (277-285 pages)
Keywords: Data protection -- Law and legislation -- Asia; Artificial intelligence -- Law and legislation -- Asia; Internet -- Law and legislation -- Asia